Secondary Complications in SCI Across the Continuum: Using Operations Research to Predict the Impact and Optimize Management Strategies - Atkins, Derek (Thomas Land Publishers, Inc., 2012)
Secondary complications following traumatic spinal cord injury (tSCI) have a tremendous impact on quality of life and health care costs. Although some complications result from the injury itself, many originate from the care provided; complications arising early in the tSCI journey can predispose an individual to recurrence later. To measure the total impact of secondary complications on patient outcomes and health care costs, all the stages of care, from first response to life in the community, must be spanned. Interventions to ameliorate secondary complications need to consider the effects on the whole system and not just individual phases of care; however, such an approach is not common in the literature. To measure the impact of complications as well as the effect of proposed interventions, a partnership between clinical researchers and operations research professionals was formed to develop a discrete-event simulation model of the entire continuum of tSCI care. In this article, we focus on the part of the model concerning common secondary complications (eg, pressure ulcers, pneumonia). We first describe early results from the model, discuss how the effects from the complications impact care throughout the tSCI continuum, and review assumptions of the model. The article concludes with a discussion as to the possible uses of the model, their strengths/limitations, and future directions.